Effect of hyaluronic acid on the development of postoperative intraperitoneal adhesions in the rat: Experimental, blinded and randomized study - Voliovici, Eduardo; Curi, Jorge (Cirugía del Uruguay, 2003)
Objetive: evaluation of the effect of hyaluronic a cid (HA) on _the deve/opment of postoperative apherences in peritonitis models in rats.Materia Is and methods: 70 rats of the Wistar species were employed, within which two study groups were designed: A) bacteria/ peitonitis through ligature and caecal puncture; and B) physica/ peritonitis through caecal abrasion. Both groups were divided into two subgroups: subgroup 1) with intraperitonea/ physio/ogic serum and subrgroup 2) with instillation of HA into the perifonea/ cavity